DETERMINATION OF PLANETOCENTRIC COORDINATES OF ALBEDO DETAILS ON SURFACE OF THE SPHERICAL PLANET AND SOME POINTS OF THE ILLUMINATED PART OF PLANET'S VISIBLE DISK UNDER VARIOUS PHASE ANGLES FROM GROUND TELESCOPIC OBSERVATIONS - Mikhalchuk, V. V. (Одеські астрономічні публікації, 2017)
The method of processing of the images of planets is based on use of auxiliary coordinate system connected with equator of intensity, is applied for determination of planetocentric coordinates of albedo details on the visible disk of the spherical planet under various conditions of its illumination. The position of a detail on the planet image is determined not relative to the center of the planet geometric disk, but relative to the center of an illuminated part of its visible disk, which permits the planetary phase influence to be excluded. By means of the given method the planetocentric coordinates of albedo details on the images of a Mercury and Mars derived from ground telescopic observations were determined. The formulae for determination of planetocentric coordinates of some basic points of the illuminated part of the visible disk of a spherical planet, in projection onto the plane of the sky, are derived. The formulae do not require attraction of auxiliary coordinate system, in spite of the fact that they are deduced from general expressions using this coordinate system.